How Do Fruit and Vegetable Markets Operate in Rural India? A Qualitative Study of the Impact of Supply and Demand on Nutrition Security. Issue 3 (September 2019) - Kehoe, Sarah H.; Dhurde, Varsha; Bhaise, Shilpa; Kale, Rashmi; Kumaran, Kalyanaraman; Gelli, Aulo; Rengalakshmi, R.; Sahariah, Sirazul A.; Potdar, Ramesh D.; Fall, Caroline H. D.
Background: Diets in rural India are cereal based with low intakes of micronutrient-rich foods. The value chains for nutrition approach aims to study supply and demand of such foods. This may aid in development of interventions to improve diets and livelihoods. Objectives: (1) To identify how fruit and vegetables are accessed, (2) to describe and map the structure of value chains for exemplar foods, (3) to understand how foods are priced, and (4) to explore factors that affect decisions about which crops are grown, marketed, and sold. Methods: After stakeholder consultation, we identified 2 fruits (mango and guava) and 2 vegetables (shepu and spinach) as exemplar foods. Criteria for these exemplar foods were that they should be known to participants and there should be variability in intakes. We held 24 interviews with value chain actors including farmers, wholesalers, and vendors of the exemplar foods. Data collection was stopped when no new information emerged. We used inductive thematic coding for our analysis. Results: The value chains for each of the exemplar foods were relatively simple and involved farmers, middlemen, and vendors at either city or village level. The main themes identified as being factors considered when making decisions about which foods to grow and sell were (1) farming resources and assets, (2) quality of produce, (3) environmental conditions, (4) financial factors, (5) transport availability, and (6) consumer demand. Conclusions: There are opportunities to intervene within fruit and vegetable value chains to increase availability, affordability, and access to produce in rural India. Future research is required to determine which interventions will be feasible, effective, and acceptable to the community and other stakeholders.